Student-as-customer discourse as a challenge to equality in Finnish higher education – the case of non-fee-paying and fee-paying master's degree students - Plamper Raakel; Siivonen Päivi; Haltia Nina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In market-oriented higher education (HE) systems, fee-paying students are positioned as customers, and studying is juxtaposed with service use. In this study, we investigate how students position themselves in relation to the student-as-customer discourse in Finnish HE, in which only students coming from outside the EU and EEA areas are charged tuition fees. We investigate the construction of the student-as-customer discourse in the narrative environment of Finnish HE through interviews with both international fee-liable and Finnish non-fee-paying master's degree students (n = 34). In addition, we analyse social differences that are constructed between fee-liable and non-fee-paying students in relation to the student-as-customer discourse. We argue that fee liability creates unequal positions for some international students and thus challenges the equality principles embedded in Finnish HE. Paradoxically, it was also found that the fee-liable student-customers have less freedom and fewer options than the non-fee-paying students.